Renal denervation decreases susceptibility of the heart to ventricular fibrillation in a canine model of chronic kidney disease. Issue 11 (4th October 2017) - Tang, Xiaotie; Shi, Lang; Cui, Xuebin; Yu, Yang; Qi, Ting; Chen, Cheng; Tang, Xianglei
Abstract : New Findings: What is the central question of this study? Renal denervation (RDN) has been shown to be effective and safe, resulting in better control of blood pressure and an improvement in left ventricular hypertrophy in chronic kidney disease (CKD) patients. Ventricular arrhythmias and sudden cardiac death are common causes of death in CKD patients, but previous studies pay almost no attention to the effects of RDN on the risk of ventricular fibrillation associated with CKD. What is the main finding and its importance? Renal denervation could decrease susceptibility of the heart to ventricular fibrillation in a canine CKD model. Improvement of left ventricular hypertrophy, sympathetic activation and inflammation by RDN may be responsible for its beneficial effects. Renal denervation (RDN) has been shown to have therapeutic value in patients with chronic kidney disease (CKD). The aim of this study was to investigate whether RDN could decrease the susceptibility of the heart to ventricular fibrillation in a canine model of CKD. Twenty‐one dogs were used. Chronic kidney disease was produced by subtotal nephrectomy in 16 dogs with RDN treatment (CKD + RDN group, n  = 8) or sham RDN (CKD group, n  = 8). Another five dogs underwent sham operation and sham RDN to serve as controls (CTR group). Parameters of renal function, blood pressure, echocardiography, ECG, noradrenaline and inflammation were measured at baseline and 6 weeks after the surgical procedure. The ventricular fibrillation threshold (VFT) was determined at the end of the study. Subtotal nephrectomy successfully induced a canine CKD model. When compared with the CTR group, subtotal nephrectomy in the CKD group significantly elevated blood pressure; increased the left ventricular mass, end‐diastolic left ventricular internal dimension, left ventricular end‐diastolic posterior wall thickness and end‐diastolic interventricular septum thickness; prolonged the QT interval, corrected QT interval, the interval from the peak to the end of the T wave (Tp‐e) and the corrected Tp‐e interval; and increased the QT dispersion and the Tp‐e/QT ratio; decreased the VFT; and increased the serum concentrations of noradrenaline, C‐reactive protein and interleukin‐6. Renal denervation significantly attenuated these changes induced by CKD. The study demonstrated that RDN could decrease the susceptibility of the heart to ventricular fibrillation in this CKD model. Improvement of left ventricular hypertrophy, sympathetic activation and inflammation by RDN may be responsible for its beneficial effects. Abstract :